Effect of the prism and Maddox rod test as the surgical target for type III acute acquired comitant esotropia - Wang, Huihang; Zheng, Weidong (Frontiers in Medicine, 2024)
Introduction: This study aims to explore more accurate and efficient examination methods to provide precise target surgical measurements for patients with type III acute acquired comitant esotropia (AACE).The study conducted a retrospective analysis of 108 patients diagnosed with AACE who received surgical treatment at the Department of Ophthalmology, the First Affiliated Hospital of Fujian Medical University, from January 2018 to September 2023. All patients underwent examinations of the deviation angle, including the Hirschberg test, prism and Maddox rod test (PMT), and prism and alternate cover test (PACT). For the PACT, the minimum value (PACTmin) and maximum value (PACTmax) were obtained based on differences in examination methods, as well as the deviation angle range (PACT range), which represents the difference between PACTmax and PACTmin. Postoperatively, these patients were followed up for at least 6 months to assess changes in eye position and whether diplopia symptoms recurred.In both near and distant examinations, the results of PACTmax were significantly greater than those of PACTmin (P < 0.001), while the deviation angles obtained from PACTmax and PMT showed no significant statistical difference (P = 0.689 (33 cm), P = 0.436 (5 m)). There was a strong linear correlation between PACTmin and PMT at both near (R = 0.8887) and distant (R = 0.8950) distances, but each PACTmin corresponded to multiple PMT values. There was no significant difference between the results of PACT range at near and distant distances (P = 0.531).The deviation angles obtained by PMT and PACTmin significantly decreased postoperatively compared to preoperative values, and diplopia disappeared in all patients, with alternative cover 上标 设置格式[驭风者]: 上标 设置格式[驭风者]: 非上标/ 下标 设置格式[驭风者]: 行距: 1.5 倍行距 设置格式[驭风者]: degree of strabismus 删除[liming [2]]:test showing no movement or presenting as an esophoria state.The PMT can provide precise target surgical measurements for type III AACE, making it a fast, effective, and cost-efficient examination method. It is worthy of being promoted and applied in clinical practice.